(untitled) (Papeles, 2024)
The application of the governability clause in the distribution of seats in provincial legislatures generates distortion in political representation. Overrepresentation in favor of the political party that wins the election and underrepresentation that harms the remaining forces. Artificial majorities are thus generated that find their justification in the need to strengthen the Executive Branches so that they have the capacity to promote their government plans. However, in recent years a series of opinions have been gaining strength that insist that governability depends not only on the majority of seats in the legislative chambers but, in addition, it is necessary to observe other conditions such as the levels of internal homogeneity of the majority coalitions, the leadership capacity of their representatives, the greater or lesser ability and/or skill to negotiate and build agreements, among other reasons. That is why we understand that it would be pertinent for this clause to be reviewed, diagramming a representation mechanism that emphasizes a new role for both the Legislative Branch and the Executive Branch in the face of a procedure for the formation and sanction of laws that contemplates different tools. to resolve eventual situations of bid or tie with respect to a legislative majority opposed to the Governor.